A novel peridynamic approach for fracture analysis of quasi-brittle materials. (1st August 2022) - Friedrich, Leandro F; Colpo, Angélica B; Kosteski, Luis E; Vantadori, Sabrina; Iturrioz, Ignacio
Abstract: In the present paper, a novel peridynamic approach is proposed to simulate the fracture behaviour of quasi-brittle materials. It consists in: (i) an improved bond force-stretch relationship to implement into peridynamic models, in order to simulate the fracture behaviour of quasi-brittle materials, and (ii) the proposal to consider, into the above models, the material energy release rate as a 3D random field, to take into account the stochastic nature of quasi-brittle material properties. Such a novel peridynamic approach is verified by analysing four case studies related to quasi-brittle materials, that is: rock, expanded polystyrene, and concrete. Graphical Abstract: Image, graphical abstract